2015
DOI: 10.2147/ijn.s76208
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of bright fluorophore core-silica shell nanoparticles by biological systems

Abstract: Nanoparticles are used in a variety of consumer applications. Silica nanoparticles in particular are common, including as a component of foods. There are concerns that ingested nano-silica particles can cross the intestinal epithelium, enter the circulation, and accumulate in tissues and organs. Thus, tracking these particles is of interest, and fluorescence spectroscopic methods are well-suited for this purpose. However, nanosilica is not fluorescent. In this article, we focus on core-silica shell nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…GQDs are simple and inexpensive in preparation as opposed to many nanoscale therapeutic delivery systems that require elaborate multistep synthesis . High quantum yield (greater than 60% for N-GQDs) intrinsic fluorescence of GQDs allows for imaging without the attachment of additional fluorophores, often used to track many other nanoparticles , and adding to their toxicity profile. GQDs show substantial biodegradability within 36 h that sets them ahead of all nonbiodegradable nanoscale platforms, accumulation of which in the cells and tissues may hinder their long-term use. ,, In addition, GQDs offer multicolor visible and visible and near-IR imaging capabilities for both in vitro and in vivo detection unlike the majority of nanoscale drug delivery platforms, or even other graphene quantum dots, , which offer imaging only in the visible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GQDs are simple and inexpensive in preparation as opposed to many nanoscale therapeutic delivery systems that require elaborate multistep synthesis . High quantum yield (greater than 60% for N-GQDs) intrinsic fluorescence of GQDs allows for imaging without the attachment of additional fluorophores, often used to track many other nanoparticles , and adding to their toxicity profile. GQDs show substantial biodegradability within 36 h that sets them ahead of all nonbiodegradable nanoscale platforms, accumulation of which in the cells and tissues may hinder their long-term use. ,, In addition, GQDs offer multicolor visible and visible and near-IR imaging capabilities for both in vitro and in vivo detection unlike the majority of nanoscale drug delivery platforms, or even other graphene quantum dots, , which offer imaging only in the visible.…”
Section: Resultsmentioning
confidence: 99%
“…GQDs are simple and inexpensive in preparation as opposed to many nanoscale therapeutic delivery systems that require elaborate multistep synthesis. 18 High quantum yield (greater than 60% for N-GQDs 52 ) intrinsic fluorescence of GQDs allows for imaging without the attachment of additional fluorophores, often used to track many other nanoparticles 69,70 and adding to their toxicity profile. GQDs show substantial biodegradability within 36 h that sets them ahead of all nonbiodegradable nanoscale platforms, accumulation of which in the cells and tissues may hinder their long-term use.…”
Section: Acs Biomaterials Science and Engineeringmentioning
confidence: 99%
“…References miRNA [68,69] siRNA [78,187] Drugs (doxorubicin, dexamethasone, betamethasone, methotrexate, caspase inhibitors, ceramide, oleanoic acid, emodin, heparin, aspirin, curcumin and sulforaphane) [66,67,79,95,103,132,147,167,189] Gene [164] The surface modifications for NP delivery, diagnostic imaging and tracking of therapeutic effects are summarized in Figure 4.…”
Section: Therapeutic Moietiesmentioning
confidence: 99%
“…Although, of course, not all of this initial dose will remain as free NMs on reaching the liver. It is also evident that NMs translocate to secondary organs following inhalation and oral administration (Smulders et al 2014;Zane et al 2015). Several investigators suggested that the extent of uptake of insoluble NMs from the GIT and airways is in the order of approximately 1-5% of the total applied dose (summarized in Kermanizadeh et al 2015), detectable in the liver as early as 24 hr post exposure (Gosens et al 2015;Thakur et al 2014).…”
Section: Summary Of In Vivo Datamentioning
confidence: 99%